A Survey on the Ethnomycology and Laboratory Analyses of Wild Mushrooms Utilized as Food Among Multicultural Groups in Selected Municipalities of Nueva Vizcaya, Philippines - Maslang, Jason Arnold (The PASCHR journal, 2021)
The study aimed to survey the different mushrooms utilized as food and medicine by the mixed ethnolinguistic groups, Novo Vizcayanos, in the province of Nueva Vizcaya. It used quantitative and qualitative methods utilizing a survey, interview, and laboratory analysis. Results showed that at least 19 wild mushroom species identified by the multicultural groups were traditionally used for food and medicine. These are the Auricularia polytrichia, Auricularia sp1, Auricularia sp. 2, Auricularia sp3, Schizophyllum commune var 1, Schizophyllum commune var 2, Termitomyces albuminosa, Termitomyces sp. 1, Termitomyces clypeatus, Termitomyces sp. 2, Termitomyces sp. 2, Termitomyces sp. 2, Kulat, Termitomyces robustus, Uong Biliit, Uong, Uong saba/uong garami, and Uong malem. In conclusion, the study provided scientific facts on the chemical and biological properties of the identified mushrooms.